Instant (rapidly hydrated) casein particle with hollow-porous microstructure and preparation method thereof

Hollow-porous casein particles are prepared by combining enzymatic modification and spray drying, solving the problem of slow wetting of casein powder and achieving rapid wetting and high solubility, which is suitable for the food processing field.

CN121176545APending Publication Date: 2025-12-23NORTHEAST AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511319923.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2025-12-23

AI Technical Summary

Technical Problem

Existing casein powders suffer from slow wetting, insufficient dispersion, and low solubility. Existing improvement methods are costly, difficult to scale up, or introduce chemical residues.

Method used

A green enzymatic modification combined with spray drying process is adopted. Casein is modified by removing amide groups through protein glutamate to form casein particles with hollow-porous microstructure, which reduces hydrophobicity and increases surface negative charge.

Benefits of technology

It significantly improves the wettability, dispersibility, and solubility of casein powder, while maintaining its nutritional quality, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121176545A_ABST
    Figure CN121176545A_ABST
Patent Text Reader

Abstract

The invention discloses an instant casein particle with a hollow-porous microstructure and a preparation method thereof. The preparation method comprises the following steps: by taking casein micelle suspension as a raw material, partially deamidating protein glutaminase under nearly neutral and mild conditions, controlling the deamidation degree (DD) to be 20-50%, carrying out thermal inactivation, and then carrying out spray drying, so as to obtain particles with hollow interiors and porous shell layers. The surface hydrophobicity of the particles is remarkably reduced, negative charges are remarkably increased, and the specific surface area and the pore volume are improved, so that rapid hydration is realized: the contact angle is less than or equal to 70 degrees at 25 DEG C within 10 seconds, the median particle size is less than or equal to 2 microns after dispersion for 30 minutes (sub-micron distribution is dominant in 60 minutes), the pH is 5-7.0, and the solubility is remarkably improved. The whole process does not need additional surfactants, the process conditions are mild, and the method is suitable for industrial implementation; the obtained product maintains the nutrition function of casein, and is suitable for high-protein instant ingredients.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of food protein processing, specifically relating to a fast-dissolving casein particle with a hollow-porous microstructure and its preparation method. More specifically, this invention relates to improving the rehydration and rapid solubility of casein powder by utilizing enzymatic modification of casein combined with spray drying technology. Background Technology

[0002] Casein-based powders exhibit poor rehydration properties, characterized by slow wetting, incomplete dispersion, and limited solubility. This has long been a technical challenge limiting the release of casein nutrients and the application of its functional properties. The root cause of these problems lies in the structure and surface characteristics of the powder: casein powders are typically prepared by spray drying, resulting in dense particle structures with highly hydrophobic surfaces. Furthermore, the highly stable micelle structure of casein makes it difficult for the powder to be promptly wetted, dispersed, and dissolved upon contact with water.

[0003] To address the aforementioned problems, existing technologies have proposed various improvement measures, such as obtaining a loose and porous powder structure through agglomeration processes, adding emulsifiers (e.g., lecithin) to the powder surface to enhance wettability, disrupting the casein micelle structure by adjusting pH and adding calcium chelating agents, and improving solubility by disrupting the dense surface of casein particles. However, these methods each have limitations: physical strategies are costly and difficult to scale up; the addition of chemical reagents can lead to chemical residues; and drastic pH treatments may damage the protein's natural structure. Therefore, none of the above methods have fundamentally solved the problem of slow rehydration of casein powder. There is an urgent need for a new technical solution that combines green enzymatic modification with microstructure regulation to significantly improve the rapid dissolution and rehydration performance of casein powder without introducing chemical reagents.

[0004] The innovation of this invention lies in the use of protein glutaminase to perform mild and green amide group removal modification on casein, combined with the commonly used industrial spray drying process, to obtain casein particles with particle microstructure and surface chemical properties that are conducive to hydration. Summary of the Invention

[0005] Objective: This invention addresses the problems of slow wetting, insufficient dispersion, and low solubility of existing casein powders by providing fast-dissolving casein particles with a hollow-porous microstructure and their preparation method. By combining green enzymatic modification with spray drying microstructure engineering, the casein particles prepared by this invention can be rapidly wetted and dissolved, significantly improving the hydration properties of casein powder while maintaining its nutritional quality. The entire process is green and environmentally friendly, suitable for industrial production.

[0006] Technical Solution: This invention provides casein particles capable of rapid hydration, characterized by a hollow-porous microstructure comprising an internal hollow cavity and a porous outer shell layer formed of casein. The shell layer is distributed with interconnected nanoscale channels, giving the particles high porosity and high specific surface area. Simultaneously, the hydrophobicity of the particle surface is significantly reduced, while the surface negative charge is significantly increased. This results in a significantly reduced contact angle between the particles and water. During dispersion, the particles can rapidly wet and release primary microparticles, and under the influence of electrostatic repulsion, quickly dissolve into a uniform and stable casein suspension.

[0007] The objective of this invention is achieved through the following technical solution: A fast-dissolving casein granule and its preparation method, comprising the following steps: (1) Preparation of casein raw material. Casein is used as the raw material. Preferably, raw milk is used as the starting material, and a micellar casein concentrate (MCC) is obtained through defatting and microfiltration. For example, fresh milk is centrifuged to remove fat, and then filtered through a microfiltration membrane to remove whey components, resulting in a concentrated milk (MCC concentrate) rich in casein micelles. The protein content of this concentrate is typically 7-10% (weight / volume), and the lactose and fat content is less than 1%. Preferably, the pH of the MCC concentrate is adjusted to approximately 6.7-6.8 (close to neutral) for later use. (2) Enzymatic partial deamidation modification. Protein glutaminase (PG) is added to the above casein micelle suspension, and an amide removal reaction is carried out under suitable conditions. The reaction is preferably carried out under near-neutral conditions, such as pH 6.5–7.5 and temperature 45–55°C. The enzyme dosage is 15–25 U / g protein, preferably about 20 U / g, based on the enzyme activity to substrate protein weight ratio (E / S). The reaction time depends on the desired degree of deamidation (DD), generally ranging from several minutes to tens of minutes. It is preferable to control the reaction time so that some glutamine residues in the casein are converted to glutamate residues, achieving a deamidation degree of 5%–50%. More preferably, controlling the deamidation degree to 20%–50% can significantly improve the hydrophilicity and charge of the protein, thereby enhancing its solubility. Once the reaction reaches the predetermined deamidation level, the reaction solution is immediately heated to 85–95°C and maintained for several minutes to terminate the enzyme reaction. (3) Spray drying to form powder. The casein suspension treated with the above enzyme is spray dried to prepare instant casein powder. Spray drying can be performed using conventional spray drying equipment, such as centrifugal or two-fluid nozzle spray drying towers. The inlet air temperature is 150-200℃, and the outlet air temperature is controlled at about 80-100℃, which can quickly remove moisture and avoid excessive thermal denaturation of protein. Preferred spray drying conditions are: inlet air temperature about 180℃, outlet air temperature about 90℃, and feed flow rate about 10-15 mL / min. Under the above conditions, casein powder with good flowability and a water content of less than 5% can be obtained. During the spray drying process, the rapid evaporation of water creates a temperature gradient, which helps to form a porous or hollow structure inside the particles. The key to this invention is to combine enzymatic modification with spray drying, so that the modification effect at the protein molecular level is transformed into advantages in the microstructure of the particles, thereby obtaining casein particles with excellent instant dissolution performance. (4) Particle Structure. The obtained powder particles exhibit a hollow, porous microstructure. Nitrogen adsorption-desorption tests confirmed that the specific surface area and pore volume of these particles were significantly higher than those of unmodified casein powder. Scanning electron microscopy (SEM) revealed tiny pores or depressions on the particle surface, and some broken particles showed internal cavities. Transmission electron microscopy (TEM) showed that the particles contained hollow cavities or a network of porous structures. The loose, porous structure of the casein particles in this invention facilitates rapid water infiltration and penetration into the particle interior. (5) Particle surface chemistry. The main component of the powder of this invention is casein, with a high protein content (dry basis protein mass fraction ≥70%). The resulting casein particles retain the additional negative charge introduced during the liquid-phase deamidation process, and the surface hydrophobicity is significantly reduced. (6) Hydration properties. The casein powder of the present invention exhibits significantly better wettability, dispersibility, and solubility in water than unmodified ordinary casein powder. Compared with unmodified powder, the contact angle is reduced by approximately 29.6%; after stirring and dispersing at 2,000 rpm for 1 hour, the particle size is reduced by approximately 99.8%; and the solubility under neutral pH conditions increases from approximately 24% to approximately 89%. Attached Figure Description

[0008] Figure 1 A comparison of the specific surface areas of different casein powder samples;

[0009] Figure 2 A comparison of pore volumes of different casein powder samples;

[0010] Figure 3 A comparison of the average pore size of different casein powder samples;

[0011] Figure 4 Scanning electron microscope (SEM) image of casein powder particles;

[0012] Figure 5 Transmission electron microscope (TEM) image of casein powder particles;

[0013] Figure 6 pH-dependent surface charge maps for different casein powder samples;

[0014] Figure 7 Comparison of surface hydrophobicity of different casein powder samples;

[0015] Figure 8 The graph shows the change of water contact angle over time from 0 to 100 seconds.

[0016] Figure 9 The graph shows the change in median particle size (D50) of the sample volume during the 60-minute dispersion process.

[0017] Figure 10 This is a particle size distribution diagram of the powder after 60 minutes of dispersion.

[0018] Figure 11 A comparison chart of the polydispersity index (PDI) of the suspensions obtained after dispersing the powder for 60 min;

[0019] Figure 12 This is a graph comparing the pH-dependent solubility of different casein powder samples. Detailed Implementation The technical solution of the present invention will be further clearly and completely described below through embodiments.

[0020] Example 1: Preparation of fast-dissolving casein particles with a hollow-porous microstructure

[0021] Step 1: Preparation of casein micelle suspension. Prepare a casein micelle suspension with a protein mass fraction of 7.74% (w / w) and adjust the pH to 7.0 using 0.1M NaOH or HCl. Incubate the suspension in a 50°C water bath and stir at 500 rpm. Then add protein glutaminase (PG enzyme, "Amano" 500, enzyme activity 500 U / g; Amano Enzyme Inc., Japan) to the suspension at a concentration of 20 U / g protein (i.e., enzyme to substrate mass ratio E / S = 1:25). After reacting for 0 min (control), 5 min, and 40 min, immediately heat the sample in a 90°C water bath for 5 min to terminate the enzyme reaction.

[0022] Step 2: Determination of Deamidation Degree (DD). The degree of deamidation in the enzyme-treated samples was determined using the ammonium ion release method. The enzyme-treated samples were centrifuged (8,000 × g, 20 min, 25 °C), and the supernatant was collected. Using an ammonia assay kit (BL1030A, Biosharp, China), the absorbance was measured at 630 nm based on the indophenol blue colorimetric method, and the amount of ammonium ions released in the sample (Sample NH4) was calculated. + Untreated casein suspension was hydrolyzed with 1M H2SO4 (1:1 v / v) at 100°C for 4 hours, and after neutralization, the total ammonium ion content (Total NH4+) was determined using the same method. + The degree of deamidation DD is calculated according to formula (1).

[0023] Step 3: Spray drying. The suspensions treated with the three enzymes were spray-dried using a Büchi B-290 laboratory spray dryer. Operating parameters were: inlet air temperature 180℃, outlet air temperature 90℃, feed rate 12mL / min (peristaltic pump rate 25%), and vacuum rate 100% (35m). 3 The atomizing air flow rate was 600 L / h. The resulting powders were named SD-4%, SD-28%, and SD-49% (corresponding to approximately 4%, 28%, and 49% deamidation degrees, respectively), and were collected and stored in a desiccator at 25°C.

[0024] Example 2: Characterization of casein powder particle structure

[0025] The particle microstructure of the three spray-dried casein powders (SD-4%, SD-28%, and SD-49%) prepared in Example 1 was characterized:

[0026] Specific surface area and porosity analysis: The specific surface area and pore characteristics of the powder were determined using a nitrogen adsorption-desorption method. Approximately 0.16 g of sample was degassed under vacuum at 40 °C for 12 hours, and then tested using a Micromeritics TriStar IIPlus specific surface area analyzer at a liquid nitrogen temperature of -195.8 °C. The specific surface area was calculated using the BET (Brunauer-Emmett-Teller) model within the relative pressure P / P0 range of 0.05–0.30; the total pore volume was estimated based on the nitrogen adsorption amount at P / P0 = 0.99; the pore size distribution was calculated using the BJH (Barrett-Joyner-Halenda) model and the DFT (density functional theory) model.

[0027] The results are as follows Figure 1As shown, the specific surface areas of the SD-4%, SD-28%, and SD-49% samples were 2.33±0.02, 17.17±0.04, and 56.64±0.06 m², respectively. 2 / g. The specific surface area of ​​the SD-49% sample was approximately 24 times larger than that of the SD-4% sample. The total pore volume increased from 0.00321 ± 0.00001 cm³ of the SD-4% sample. 3 / g significantly increased to 0.05655±0.00002cm in the SD-49% sample. 3 / g (e.g.) Figure 2 As shown, the increase is approximately 16.6 times, while the average pore size decreases from 5.51±0.02nm to 3.99±0.01nm (as shown). Figure 3 As shown, the reduction was approximately 27.6%. This result indicates that with the increase in the degree of deamidation, a finer and more developed nanoscale pore network was formed inside the particles.

[0028] Microscopic morphology observation (SEM): After gold sputtering, the particle morphology was observed using a Hitachi SU3800 scanning electron microscope at an accelerating voltage of 5kV.

[0029] The results are as follows Figure 4 As shown (multipliers 6,000× and 9,000×), the SD-4% sample has a dense particle morphology with wrinkled surfaces; the SD-28% sample has relatively loose particles with smooth surfaces; while the SD-49% sample has significantly expanded particles with smooth surfaces, and pore structures formed due to the rupture of internal cavities can be observed (indicated by red arrows), indicating that hollow cavities have been formed inside.

[0030] Internal structure hollowness verification (TEM): An appropriate amount of powder sample was dispersed in 95% ethanol (concentration 0.3 mg / mL), sonicated for 5 min, and then 5 μL of the suspension was dropped onto a copper mesh. After adsorption for 60 s, negative staining was performed with 2% (w / v) uranium acetate for 45 s. The internal structure was observed using a Hitachi HT7820 transmission electron microscope at an accelerating voltage of 100 kV.

[0031] The results are as follows Figure 5 As shown, the SD-4% sample has a dense and solid interior; the SD-28% sample shows an electronically transparent and loose region; and the SD-49% sample exhibits a typical "core-shell" structure with a huge electronically transparent hollow core and a thin electronically dense protein shell, directly proving the formation of the hollow structure.

[0032] Example 3: Characterization of the chemical properties of particle surfaces

[0033] The surface chemical properties of the three spray-dried casein powders (SD-4%, SD-28%, and SD-49%) prepared in Example 1 were characterized:

[0034] Surface hydrophobicity: The surface hydrophobicity of particles was determined using the LANS fluorescent probe method. Samples were prepared into a series of protein solutions ranging from 0.04375 to 0.7 mg / mL using PBS buffer (pH 6.8). 4 mL of each protein solution was added to 20 μL of LANS fluorescent probe solution (2.4 mg / mL, PBS solvent), vortexed, and reacted in the dark for 15 min. The fluorescence intensity of each sample was measured using a Hitachi F-7000 fluorescence spectrophotometer under conditions of excitation wavelength 390 nm, emission wavelength 470 nm, and slit width 5 nm. A graph of fluorescence intensity versus protein concentration was plotted; the slope of the initial linear region represents the surface hydrophobicity parameter H0.

[0035] The results are as follows Figure 6 As shown, the H0 value of the SD-4% sample was 30053±75, while the H0 value of the SD-49% sample decreased significantly to 5970±67, a decrease of approximately 80.1%. This indicates that the deamidation reaction greatly improves the hydrophilicity of the particle surface.

[0036] Surface charge (Zeta potential): The sample was prepared into a 0.1% (w / v) aqueous suspension. The pH was adjusted to the full value in the range of 3.0-10.0 with 0.1M HCl or NaOH. After equilibration at 25℃ for 30 min, the zeta potential of the sample under each pH condition was determined by laser Doppler microelectrophoresis using a Malvern Zetasizer Nano ZS90 nanoparticle size and potential analyzer.

[0037] The results are as follows Figure 7 As shown, across the entire test pH range, samples with higher deamidation degrees carried a greater amount of negative charge. The SD-49% sample was negatively charged throughout the pH range, and its absolute zeta potential at neutral pH 7.0 was significantly higher than that of the SD-4% sample. This demonstrates that the additional carboxyl groups (-COO-) introduced by the deamidation reaction were retained, significantly increasing the negative charge density on the particle surface. These results indicate that the casein particles prepared in this invention exhibit significantly enhanced surface hydrophilicity and negative charge, laying the foundation for their excellent rapid solubility.

[0038] Example 4: Hydration Characteristics

[0039] The hydration properties of the three spray-dried casein powders (SD-4%, SD-28%, and SD-49%) prepared in Example 1 were characterized, including indicators such as wettability, dispersibility, and solubility:

[0040] Wetting properties: The powder was compressed into smooth circular tablets under a pressure of 5 MPa for 30 s. Using a contact angle meter (SDC-350H type), the test was conducted at room temperature. 5 μL of distilled water was dropped onto the tablet surface, and the static contact angles were recorded at 0, 2, 4, 5, 10, 30, 60, and 90 s after the water droplet fell.

[0041] The results are as follows Figure 8 As shown, the SD-49% sample had the lowest initial contact angle (77.3 ± 0.45°) and a contact angle of 57.9 ± 0.51° at 10 s; in contrast, the SD-4% sample had a stable contact angle of 82.2 ± 0.32° at 10 s. Compared to the SD-4% sample, the SD-49% sample showed an improvement in final wetting performance of approximately 29.6%.

[0042] Dispersibility: Approximately 1 g of powder was dispersed in 100 mL of distilled water (25°C) and stirred at 2000 rpm in the dispersion unit of a HORIBALA-350 laser particle size analyzer. Monitoring was performed continuously for 60 min, with the volume-weighted median particle size (D50) recorded every 2.5 min. Results are as follows: Figure 9 As shown, the SD-49% sample had the smallest initial D50 particle size (16.4 ± 0.82 μm), and after 60 min of stirring, its D50 particle size decreased to approximately 0.05 μm; while the D50 of the SD-4% sample decreased from 71.5 μm to 23 μm. The particle size of the SD-49% sample decreased by approximately 99.8%, and its dispersion effect was far superior to that of the SD-4% sample. The suspension after 60 min of dispersion was diluted to 0.1% (w / v), and the hydrodynamic size distribution and polydispersity index (PDI) of the particles were determined by dynamic light scattering (DLS) using a Malvern Zetasizer Nano ZS90 instrument.

[0043] The results are as follows Figure 10 and Figure 11 As shown, the SD-49% sample has a narrow particle size distribution (range of approximately 59-361 nm) and a PDI as low as 0.29, indicating the formation of a uniform and stable nanoscale dispersion; while the SD-4% sample has a wider particle size distribution and multiple peaks (range of approximately 2990-3477 nm), a PDI of 1, and poor dispersibility.

[0044] Solubility: Prepare a 1% (w / v) aqueous suspension of the powder. Adjust the pH to integer values ​​within the range of 3.0-10.0 using 0.1M HCl or NaOH. After equilibration at 25°C for 30 min, centrifuge (8,000×g, 20 min, 25°C) and collect the supernatant. Determine the protein concentration in the supernatant using the BCA Protein Assay Kit (BL1020A, Biosharp, China). Calculate the solubility based on the total amount of protein completely dissolved in 0.1M NaOH.

[0045] The results are as follows Figure 12 As shown, under neutral pH 7.0 conditions, the solubility of the SD-49% sample was as high as 89.0 ± 2.54%, while the solubility of the SD-4% sample was only 24.0 ± 1.64%, an absolute increase of 65 percentage points. Even under conditions close to the isoelectric point at pH 5.0, the solubility of the SD-49% sample (32.0%) was still significantly higher than that of the SD-4% sample (18.0%).

Claims

1. A process for the preparation of instant (fast hydrating) casein protein particles having a hollow-porous microstructure, characterized in that, Includes the following steps; (1) Enzymatic modification step: Prepare a casein solution with a mass concentration of 7% to 10% by water, and add protein glutaminase under suitable conditions to carry out enzymatic deamidation, so that the deamidation degree of casein reaches 20% to 50%, thereby improving the hydrophilicity of casein and increasing its net negative charge. (2) Spray drying pore-forming step: The solution obtained in step (1) after deamidation treatment is directly spray dried without adding pore-forming agent, foaming agent or crosslinking agent. The inlet air temperature is 150-180℃ and the outlet air temperature is 60-90℃. The electrostatic repulsion between protein molecules enhanced by the deamidation treatment works in conjunction with the solute migration during the drying process to spontaneously form fast-dissolving (rapidly hydrated) casein particles with hollow-porous microstructure, without the need for freeze drying or spray freeze drying steps. (3) The optimal conditions for preparation are: a casein suspension with a casein content of 7.74% is deamidated by protein glutaminase (50℃, 500rpm, 20U / g) to obtain a casein suspension with a deamidation degree of 49%, which is then spray-dried (inlet air temperature 180℃, outlet air temperature 90℃, feed rate 12mL / min) to obtain casein particles.

2. A porous protein powder particle mainly composed of casein, obtained by the preparation method according to claim 1, characterized in that, Includes the following elements: (1) Protein composition: The casein in the particles has undergone partial deamidation treatment, with a deamidation degree of 5% to 50%; (2) Pore structure: the particles have a porous structure formed by the synergistic effect of the electrostatic repulsion between protein molecules during the spray drying process and solute migration, with a specific surface area of 10 to 80 m 2 / g, and a pore volume of 0.01 to 0.5 cm 3 / g; (3) Surface characteristics: The surface hydrophobicity of the particles is less than 30000 (H0), the contact angle with water is 20° to 70°; and the zeta potential under pH 7.0 conditions is -20mV to -50mV; (4) Solubility: During the dispersion process, the primary particles are rapidly released, and the solubility in water at 25°C after stirring for 30 minutes is not less than 50%. (5) The optimal casein micelles obtained from the optimal preparation condition of step (3) in claim 1 comprise the following characteristics: specific surface area (56.64 ± 0.06 m 2 / g), total pore volume (0.05655 ± 0.00002 cm 3 / g), average pore size (3.99 ± 0.01 nm), surface hydrophobicity (Ho, 5970 ± 67), zeta potential (pH 7.0, -31 mV), water contact angle (10 seconds, 57.9 ± 0.51°), solubility (pH 7.0, 89.0 ± 2.54%), average particle size after dispersion (D50, 60 minutes, 134 nm).